1993
DOI: 10.1161/01.cir.88.6.2623
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular fusion during resetting and entrainment of orthodromic supraventricular tachycardia involving septal accessory pathways. Implications for the differential diagnosis with atrioventricular nodal reentry.

Abstract: The relative proximity (conduction time) among pacing site, site of entrance to a reentrant circuit, and site of exit from the circuit to the paced chamber are critical for the occurrence of fusion during resetting and/or entrainment. The presence or absence of fusion during these phenomena can help in the differential diagnosis of certain supraventricular tachycardias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…The use of tachycardia entrainment via ventricular pacing for differential diagnosis of supraventricular tachycardias was introduced by Ormaetxe et al 34 Right apical stimulation is relatively close to the insertion of a septal accessory pathway as opposed to the AV junction; thus, ventricular fusion during resetting or entrainment of tachycardia has been reported to occur in patients with AVRT due to septal pathways but not with AVNRT. 34 Michaud et al 35 have proposed 2 additional criteria for differential diagnosis.…”
Section: Tachycardia Entrainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of tachycardia entrainment via ventricular pacing for differential diagnosis of supraventricular tachycardias was introduced by Ormaetxe et al 34 Right apical stimulation is relatively close to the insertion of a septal accessory pathway as opposed to the AV junction; thus, ventricular fusion during resetting or entrainment of tachycardia has been reported to occur in patients with AVRT due to septal pathways but not with AVNRT. 34 Michaud et al 35 have proposed 2 additional criteria for differential diagnosis.…”
Section: Tachycardia Entrainmentmentioning
confidence: 99%
“…34 Michaud et al 35 have proposed 2 additional criteria for differential diagnosis. The ventriculoatrial (VA) interval and tachycardia cycle length (TCL) were measured during tachycardia, and entrainment of the tachycardia was accomplished with RV apical pacing.…”
Section: Tachycardia Entrainmentmentioning
confidence: 99%
“…These factors make the differential diagnosis challenging. [8][9][10] Electrical stimulation is widely used in electrophysiology. [11][12][13] His bundle refractory period pacing is used to differentiate AVNRT from ORT.…”
Section: Discussionmentioning
confidence: 99%
“…Several diagnostic maneuvers can aid differential diagnosis, including a return cycle after continuous entrainment from the right ventricular apex (RVA), 1,2 tachycardia resetting with electrocardiographic fusion, 3,4 and even responses to single ventricular extrastimulus.5 However, it has been reported that ≤15% to 20% of the tachycardia mechanism could be interrupted by the entrainment maneuvers. 5 In these instances, the utility of RVA pacing during tachycardia at the beginning of the entrainment attempt has received less attention as a diagnostic technique.…”
mentioning
confidence: 99%
“…Several diagnostic maneuvers can aid differential diagnosis, including a return cycle after continuous entrainment from the right ventricular apex (RVA), 1,2 tachycardia resetting with electrocardiographic fusion, 3,4 and even responses to single ventricular extrastimulus.…”
mentioning
confidence: 99%